Remapping emergent Islam: Texts, social settings, and ideological trajectories - Segovia, Carlos A. (Social Worlds of Late Antiquity and the Early Middle Ages, 2020)
This multidisciplinary collective volume advances the scholarly discussion on the origins of Islam. It simultaneously focuses on three domains: texts, social contexts, and ideological developments relevant for the study Islam's beginnings - taking the latter expression in its broadest possible sense. The intersections of these domains need to be examined afresh in order to obtain a clear picture of the concurrent phenomena that collectively enabled both the gradual emergence of a new religious identity and also the progressive delimitation of its initially fuzzy boundaries